Anthropogenic Pressures in Temporary Streams: the importance of environmental drivers. - Matono, Paula (2015)
Mediterranean temporary streams show high spatial and temporal heterogeneity. Native fish species are adapted to this natural variability, but the cumulative effect of natural and anthropogenic disturbances may compromise the stability and persistence of fish assemblages. This study aimed to determine if environmental drivers affect the response of fish assemblages to anthropogenic pressures in temporary streams and identify what type of fish assemblages are particularly vulnerable to anthropogenic disturbance. Data were collected from 22 sites located in southern Portuguese temporary streams between 1996 and 2012. The temporal pattern of fish assemblages in each site was used to examine fish assemblage stability, that is, the relative constancy of species abundance over time, quantified using the Bray–Curtis similarity coefficient. Native fish assemblage stability was positively associated with altitude, annual rainfall, percentage of riffles and habitat diversity and highly negatively related to anthropogenic pressure, particularly land use intensification, riparian degradation, sediment load and organic contamination/nutrient enrichment. Results highlighted an interaction between natural environmental and anthropogenic pressure gradients; anthropogenic disturbance tends to be lower in high-elevation headwater streams and increases in lowland streams, particularly in downstream reaches. In upstream reaches, especially in lowland streams, fish assemblage stability showed a steep decline with the increase in anthropogenic pressure. Lowland downstream reaches displayed a less steep decline of fish assemblage stability in response to degradation, despite having greater anthropogenic disturbance. The results highlight the particular vulnerability of headwater streams in lowland sectors to anthropogenic disturbance.